Simulation analysis of key technology optimization of 5G mobile communication network based on Internet of Things technology - Guo Yan (International Journal of Distributed Sensor Networks)
With the rapid development of mobile Internet and Internet of Things business, the 5G mobile communication process has been accelerated. This article summarizes the Internet technology under 5G mobile communication, analyses the connotation of Internet of Things, and studies the integration of 5G mobile communications and Internet of Things technology. Through the analysis and discussion of the new possibilities in the Internet of Things era under 5G mobile communication technology, the research shows that the simulation analysis combined with the cell breathing technology and the base station dormancy technology aims to decrease the energy consumption of the base station under the premise of ensuring the communication quality, thereby improving the network energy efficiency. Research shows that in the dense and uniform user distribution scenario, the power consumption has a small decrease due to the increase of power consumption, but the system capacity is significantly improved and the communication quality is improved. It can ensure the user’s fairness and system capacity to achieve, and meet the rate requirements of different users. The analog results verify the accuracy of the theoretical analysis.